Sebuah artikel Analisis Peran Dinas Perindustrian Perdagangan Energi dan Sumber Daya Mineral Provinsi Sumatera Utara dalam Pengembangan Usaha Kecil Menengah (UKM) dalam Perspektif Ekonomi Islam - Fenni Windi Yati; Andri Soemitra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Small and Medium Enterprises have an important role in the development of the Indonesian economy and as a factor shaping the regional economy. There are around 2.5 million small and medium enterprises in the North Sumatra Government spread across various regions. The purpose of writing this article is to find out the extent of the role of the Department of Industry and Trade in developing the small and medium enterprise sector. The method used is qualitative research by means of field observation, interviewing resource persons, and supported by similar books and articles. The results of this study, the role of the trade industry office in local economic development, especially in the city of Medan, is very important, including the development of the business and service sector evenly and empowerment in the industrial, agricultural and non-agricultural sectors. Islam has its own principles for equal distribution of human welfare. So it can be concluded that the development of small and medium enterprises can affect the speed of economic growth and the role of the government is needed to encourage it to be more advanced.